Occurrence of CTX-M Producing Escherichia coli in Soils, Cattle, and Farm Environment in France (Burgundy Region) - Hartmann, Alain; Amoureux, Lucie; Locatelli, Aude; Depret, Geraldine; Jolivet, Claudy; Gueneau, Eric; Neuwirth, Catherine (Frontiers in Microbiology, 2012)
CTX-M (extended spectrum beta-lactamase- ESBL) producing Escherichia coli are increasingly involved in human infections worldwide. The aim of this study was to investigate potential reservoirs for such strains: soils, cattle and farm environment. The prevalence of blaCTX-M genes was determined directly from soil DNA extracts obtained from 120 sites in Burgundy (France) using real time PCR. blaCTX-M targets were found in 20% of the DNA extracts tested. Samples of cattle feces (n=271) were collected from 182 farms in Burgundy. Thirteen ESBL-producing isolates were obtained from 12 farms and further characterized for the presence of bla genes. Of the 13 strains, five and eight strains carried blaTEM-71 genes and blaCTX-M-1 genes respectively. Ten strains of CTX-M-1 producing E. coli were isolated from cultivated and pasture soils as well as from composted manure within 2 of these farms. The genotypic analysis revealed that environmental and animal strains were clonally related. Our study confirms the occurrence of CTX-M producing E. coli in cattle and reports for the first time the occurrence of such strains in cultivated soils. The environmental competence of such strains has to be determined and might explain their long term survival since CTX-M isolates were recovered from a soil that was last amended with manure one year before sampling.